Dihypoiodites stabilised by 4-ethylpyridine through O–I–N halogen bonds. Issue 42 (21st October 2021) - Kramer, Eric; Yu, Shilin; Ward, Jas S.; Rissanen, Kari
Abstract : Several neutral bis (O–I–N) compounds were synthesised incorporating various dihypoiodites and 4-ethylpyridine, which were characterised in both the solution and solid states. Abstract : Four bis (O–I–N) compounds have been synthesised from various dihypoiodites and 4-ethylpyridine. The compounds were characterised in both the solution and solid states by NMR spectroscopy ( 1 H, 15 N), X-ray diffraction, and computational calculations.